Efficient exosome delivery in refractory tissues assisted by ultrasound-targeted microbubble destruction - Wenqi Sun; Zhelong Li; Xueying Zhou; Guodong Yang; Lijun Yuan (Taylor & Francis Group, 2019)
Recently, exosomes have been emerged as promising drug delivery carriers, while certain tissues are intrinsically resistant to exosomes. Therapeutically improving the drug delivery efficiency in these tissues/organs would certainly broaden the potential application of exosomes in future. Ultrasound-targeted microbubble destruction (UTMD) is a promising technique for non-invasive, targeted drug delivery. In this study, we explore the possibility that UTMD assists exosome delivery in these intrinsically resistant tissues. Mice were subjected to tail vein injection of DiR-labeled exosomes together with/without UTMD of SonoVueTM, followed by in vivo and ex vivo tracking of the exosomes. As expected, heart, adipose tissue, and skeletal muscle were found reluctant to exosomes from different origins. Targeted destruction of the ultrasound microbubbles (SonoVueTM) in the heart and adipose tissue region significantly increased the exosome infiltration and endocytosis there, as revealed by fluorescence imaging and confocal laser scanning microscope (CLSM). UTMD treatment 1 h prior to exosome injection failed to facilitate the exosome endocytosis in the targeted region, indicating that the transient promoting effects of UTMD. Moreover, increases of UTMD (numerous pulses) did not linearly enhance the exosome delivery. Together, our study here has established a novel strategy for targeted delivery of exosomes in the reluctant tissues, by combining the advantages of ultrasound microbubbles and exosomes in drug delivery.